Public Discourse on Toll Road Services During the Eid Homecoming: A Topic Modelling and Agenda Rippling Analysis - Faiza Riani (INJECT (Interdisciplinary Journal of Communication), 2025)
This study examines the digital discourse regarding toll road services during the 2025 Eid homecoming using Topic Modeling with the Latent Dirichlet Allocation (LDA) method, grounded in the Reverse Agenda-Setting theory and the concept of Agenda Rippling. Data were collected from conversations on the social media platform X (Twitter) during the period from seven days before to seven days after Eid (March 24-April 8, 2025). The analysis identified three main issues: direct user experiences related to traffic conditions, driving behavior, and accidents (Topic 6); official communications from relevant authorities such as the Police and Jasa Marga (Topic 8); and public disappointment due to the gap between expectations and the actual quality of toll road services (Topic 3). This study employs Reverse Agenda-Setting Theory and the concept of Agenda Rippling to explain how public opinion can reshape the direction of media communication. The findings highlight the importance of monitoring digital public discourse to address the informational needs and aspirations of society, particularly in strategic moments such as the Eid homecoming season.